Health Education Materials for Arab Patients: Content and Design Preferences - Hashim, Muhammad Jawad; Mustafa, Halla; Al Abdouli, Amani Obaid; Abdulla Al, Reem Ahmed; AlQahtani, Salama Mohamed; Almajed, Salama Abdulbasit; Alzaabi, Shamma Saif; Alkaabi, Mariam Salem (Medical principles and practice, 2013)
Objective: To investigate the content and design preferences of printed health education leaflets among Arab patients. Materials and Methods: A survey questionnaire to 17 subjects (women: n = 8, men: n = 9; age range 17-70 years) and three focus-group discussions (total 16 participants) were used to assess preferences by showing samples of Arabic health education materials. The questionnaire was administered by interviewers. For the focus-group discussions, the sessions were conducted by a trained interviewer, audio recorded and analyzed thematically. The subjects' educational level was from no formal schooling to university level. Results: In survey component, all patients preferred photographs over clipart. Typeface (‘font') preferences were for Simplified Arabic in 8 subjects (47%) and Mudir MT in 7 (41%); the 16-point font size was favored by 14 (82%) patients. In the three focus-group discussions, themes that participants expressed included use of standard Arabic with local dialects, short sentences, and culturally appropriate advice with practical and quantifiable examples. Conclusions: The participants preferred health education materials to be color trifold brochures illustrated with pictures and not clipart and written in Arabic using the Simplified Arabic font in 16-point size.